Perilaku Prososial dan Bimbingan Islam - Muhammad Huzain (TASAMUH: Jurnal Studi Islam, 2020)
Islamic Shari'ah has social goals that must be realized in every society, even if it is limited between individuals in an environment, association in travel, meetings in houses of worship, or even brief encounters in a seminar. These social goals must also be realized in permanent communities such as families, micro communities, macro societies in a nation or even the whole community. Islam is very concerned about social life for its adherents. Even its existence has succeeded in elevating human dignity. Activities that contain social values ​​are always put forward by Islam. For example, the issue of zakat, carity, social life and others always get a high portion of attention, especially in providing equality and equity between men and women. In relation to humans are social creatures, who cannot live alone.